STUDY ON THE VARIABILITY OF BLAZAR 3C345 IN RADIO FREQUENCY RANGE - Sukharev, A. (Одеські астрономічні публікації, 2013)
3C345 - intensively studied for many years in a wide range of the electromagnetic spectrum. Since 1965, the RT-26 radio telescope of the University of Michigan at frequencies of 14.5, 8 and 4.8 GHz conducted long-term monitoring of the radio source. Applied method of wavelet- analysis, allowed investigating changes in the harmonic signal components over time. For the main trend component period is 16 - 6 years, for the short-time component: 4.7 - 1.7 years. Based on global wavelet spectra in frequency range, calculated "spectra periods", characterizing the basic phases of the source activity and compared with VLBI.